2011
DOI: 10.1542/peds.2009-3095
|View full text |Cite
|
Sign up to set email alerts
|

Apparent Life-Threatening Events in Presumably Healthy Newborns During Early Skin-to-Skin Contact

Abstract: The death or near death of a presumably healthy newborn in the delivery room is uncommon. We report here 6 cases of apparent life-threatening events (ALTEs) in the delivery room during the first 2 hours of life. In each case, the incident occurred in a healthy infant who was in a prone position on his or her mother's abdomen during early skin-to-skin contact. In most cases, the mother was primiparous, and in all cases the mother and infant were not observed during the initiation of skin-to-skin contact and bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
63
0
10

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(77 citation statements)
references
References 17 publications
4
63
0
10
Order By: Relevance
“…This is most commonly observed in the infants of primiparous mothers who are unobserved by medical or nursing staff and undergoing a period of skin-to-skin contact, with the infant prone or on the side on the mother's chest. This association has been reported previously in studies from Germany,3 France46 and Scotland,7 and the presence of evidence of prenatal brain injury in one infant in the Scottish study suggests that prenatal compromise may be a contributing factor in some infants, even in the absence of evidence of intrapartum asphyxia or the need for resuscitation at birth. The circumstances in which the collapse has occurred in many instances is suggestive of accidental asphyxia,2 3 6 but surprisingly, the German study found that most mothers were awake at the time of the collapse, most had not been given sedative medication recently and most mothers had observed their infant to be apparently well less than 30 min before the collapse 3…”
supporting
confidence: 84%
“…This is most commonly observed in the infants of primiparous mothers who are unobserved by medical or nursing staff and undergoing a period of skin-to-skin contact, with the infant prone or on the side on the mother's chest. This association has been reported previously in studies from Germany,3 France46 and Scotland,7 and the presence of evidence of prenatal brain injury in one infant in the Scottish study suggests that prenatal compromise may be a contributing factor in some infants, even in the absence of evidence of intrapartum asphyxia or the need for resuscitation at birth. The circumstances in which the collapse has occurred in many instances is suggestive of accidental asphyxia,2 3 6 but surprisingly, the German study found that most mothers were awake at the time of the collapse, most had not been given sedative medication recently and most mothers had observed their infant to be apparently well less than 30 min before the collapse 3…”
supporting
confidence: 84%
“…An apparent lifethreatening episode, or what may be referred to as a brief resolved unexplained event, may be low risk and require simple interventions such as positional changes, brief stimulation, or procedures to resolve airway obstruction. 46,53 Falls are another concern in the immediate postnatal period. Mothers who are awake and able to respond to their newborn infant immediately after birth may become suddenly and unexpectedly sleepy, ill, or unable to continue holding their infant.…”
Section: Safety Concerns Regarding Immediate Sscmentioning
confidence: 99%
“…Ces arguments ont permis de recommander la pratique du peau-à-peau dès la naissance, que ce soit par l'Organisation mondiale de la santé (OMS) au niveau international ou par la Haute Autorité de santé (HAS) en France [14]. Cependant, certains évènements indésirables ont été rapportés et notamment des malaises graves [15][16][17][18]. Certains points communs existent dans les différentes observations : l'existence d'un intervalle libre entre l'adaptation normale à la vie extrautérine et la découverte du malaise du nouveau-né, ainsi que la survenue précoce de l'incident au cours des toutes premières heures de vie, en particulier en salle de naissance [17,19].…”
Section: Introductionunclassified
“…Cependant, certains évènements indésirables ont été rapportés et notamment des malaises graves [15][16][17][18]. Certains points communs existent dans les différentes observations : l'existence d'un intervalle libre entre l'adaptation normale à la vie extrautérine et la découverte du malaise du nouveau-né, ainsi que la survenue précoce de l'incident au cours des toutes premières heures de vie, en particulier en salle de naissance [17,19]. Si la formation du personnel, l'information et l'implication des parents permettent une certaine prévention, l'intérêt d'une surveillance de la saturation pulsée en oxygène (SpO 2 ) peut être discuté.…”
Section: Introductionunclassified